The development of a systematic ultrasound protocol facilitates the visualization of foreign bodies within the canine distal limb - Schoenfeld, Ebony; Combs, Martin; Callcott, Esther; Jermyn, Kieri; Rotne, Randi (Frontiers in Veterinary Science, 2023)
Ultrasonography is an excellent investigative tool that can assist with the diagnosis of soft tissue conditions. In human medicine, ultrasonography is a fundamental diagnostic tool for the investigation of suspected vegetal foreign bodies (VFB), with protocol-based ultrasonography providing increased accuracy compared to lesion-focused examinations. Protocol-based ultrasonography is an emerging tool within the veterinary field, however, compared to human medicine is not routinely employed. The objective of this study was to develop a systematic ultrasound protocol to examine the distal limb for the visualization of vegetal foreign bodies (SUEDVEG). A 12MHz linear and an 18MHz high-frequency small-footprint linear array transducer was used on cadaver forelimbs (n=6) and hindlimbs (n=6) with images obtained from three common foreign body locations within the distal limb; 1; the interdigital webbing, 2; the palmar/plantar aspect of the phalanges and metacarpus and 3; the dorsal region of the phalanges and metacarpus. From these images, a 13-step systematic musculoskeletal protocol was developed and utilized on eight clinical cases or 10 limbs that had signs typical of distal limb VFB to preliminarily validate the proposed method. Vegetal foreign bodies were successfully identified and retrieved in seven (n=8) clinical cases with method steps 9 and 11 (orthogonal views) identifying the majority of VFBs. The described ultrasound method appears highly sensitive useful for visualizing soft tissue locations of the canine distal limb known for tracking foreign bodies. Further studies are required to validate the described systematic examination method as the preferred clinical protocol over currently used lesion-focused exploration techniques.